2000
DOI: 10.1128/aac.44.8.2068-2076.2000
|View full text |Cite|
|
Sign up to set email alerts
|

Dose-Dependent Pharmacokinetics of Amphotericin B Lipid Complex in Rabbits

Abstract: Amphotericin B lipid complex (ABLC) was recently approved by the Food and Drug Administration for treatment of patients with invasive fungal infections who are intolerant of or refractory to conventional amphotericin B therapy. Little is known, however, about the pharmacokinetics of this new antifungal compound. We therefore investigated the pharmacokinetics of ABLC in comparison with those of conventional desoxycholate amphotericin B (DAmB) in rabbits. The pharmacokinetics of DAmB in a rabbit model were simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 14 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Most preclinical studies consistently indicate that liposomal AmB increases drug disposition in organs such as the lung and central nervous system [ 380 , 381 , 382 ]. Clinical trial results, on the other hand, indicate that liposomal AmB and AmB lipid complexes have better bioavailability, tolerability, and safety compared with AmB deoxycholate [ 207 , 208 , 383 , 384 , 385 ]. Studies conducted in patients have shown the presence of high concentrations of liposomal AmB in the liver, spleen, kidney, thyroid, bone marrow, and lung [ 386 ].…”
Section: Clinical Use Of Polyenesmentioning
confidence: 99%
“…Most preclinical studies consistently indicate that liposomal AmB increases drug disposition in organs such as the lung and central nervous system [ 380 , 381 , 382 ]. Clinical trial results, on the other hand, indicate that liposomal AmB and AmB lipid complexes have better bioavailability, tolerability, and safety compared with AmB deoxycholate [ 207 , 208 , 383 , 384 , 385 ]. Studies conducted in patients have shown the presence of high concentrations of liposomal AmB in the liver, spleen, kidney, thyroid, bone marrow, and lung [ 386 ].…”
Section: Clinical Use Of Polyenesmentioning
confidence: 99%
“…Moreover, given the pharmacokinetic and pharmacodynamics properties of high-dose L-AmB with its associated long half-life and a dose-dependent efficacy against Candida species, these delivery procedures would allow an optimization of the concentrations at the site(s) of infection(s). [ 18 , 19 ] Such administration regimen was only evaluated in an hematological patient population for the prophylaxis of invasive fungal infections[ 20 , 21 ], or in the treatment of invasive aspergillosis [ 19 , 22 ]. It has also been studied for prophylaxis in patients undergoing liver transplantation[ 23 ], in treatment of visceral leishmaniasis in the HIV patient population[ 24 ], treatment of mucormycosis[ 25 ], or even in the neonates setting [ 26 ].…”
Section: Introductionmentioning
confidence: 99%